(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Internal control system is a safety valve that preserves economic units assets and ensure the accuracy of financial data, as well as to obligation in the laws, regulations, administrative policies ,and improve the efficiency, effectiveness and economic of operation, so it has become imperative for these units attention to internal and developed control system The research problem in exposure the economic units when the exercise of their business to many of the risks to growth or hinder the achievement of its objectives and the risks (financial, operational, strategy, risk) and not it rely on risk Assessment according to modern scientific methods, as in Brown’s risk Classification, Which led to the weakness of the internal control identifying risks to the various activities lead to failure to achieve the goals established for it. Evaluate the internal control in Karbala University accordance with the classification of Brown risks and finished to a set of conclusions and recommendations